2019
DOI: 10.1136/archdischild-2019-nppc.60
|View full text |Cite
|
Sign up to set email alerts
|

P051 The bigger you are the harder you fall? Short term effects of LUM/IVA (Orkambi) on lung function in children with cystic fibrosis

Abstract: AimCystic Fibrosis conductance Transmembrane Regulator (CFTR) protein modulators represent a major breakthrough in the pharmacological management of Cystic Fibrosis (CF). Previous studies report acute changes in lung function after first administration of lumacaftor/ivacaftor (LUM/IVA) without a clear underlying mechanism.1 2 Our aim was to explore links between changes in percent predicted forced expiratory volume in one second (ppFEV1) and a number of potentially influencing factors.MethodsWe conducted a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A retrospective study by Grady et al in 2019 also supported the research mentioned above. The study group's 15 patients showed a lower rate in FEV1 after therapy with LUM/IVA [19]. Figure 3 shows the overall outline of the drug's effect on the lung.…”
Section: Changes In Fev1mentioning
confidence: 96%
“…A retrospective study by Grady et al in 2019 also supported the research mentioned above. The study group's 15 patients showed a lower rate in FEV1 after therapy with LUM/IVA [19]. Figure 3 shows the overall outline of the drug's effect on the lung.…”
Section: Changes In Fev1mentioning
confidence: 96%